THE MODEL OF PROFESSIONAL COMPETENCE OF A SPECIALIST - Barpybaev, T. R.; Toktomambetova, J. S. (Bulletin of Issyk-Kul University, 2024)
The article considers the stages, levels, contents of scientific research and concepts such as model, modeling, ways to create a model of professional competence. The stages of creating models of competencies and competence, the concept of interdisciplinarity are also considered. The article describes in detail the stages, properties and tasks of the professional competence model of a specialist. We note that for the training and development of the student at each stage of the educational process, it is necessary to separately compile models of competencies and competence for the implementation of these stages. At the substantive stage of the study, the collection of quantitative knowledge continues, giving the possibility of an objective report, until its completion. In this case, the features, properties and functions of the structure of the object can be studied using universal mathematical-cybernetic methods and models. The tools and means of formal-structural analysis, which form the basis of the methods and models of the study, can be used to study this specific subject.